Talk it Out: Helping Students Conquer Statistics Anxiety - Cesario, Brian (International Journal For Research In Educational Studies, 2019)
In this paper, the author discusses a multi-component strategy used to help graduate social science students overcome feelings of anxiety that traditionally accompany enrollment in statistics courses.